Impact of 18F-FDG PET/MR on therapeutic management in high risk primary breast cancer patients – A prospective evaluation of staging algorithms. Issue 128 (July 2020) - Kirchner, Julian; Martin, Ole; Umutlu, Lale; Herrmann, Ken; Bittner, Ann-Kathrin; Hoffmann, Oliver; Mohrmann, Swetlana; Gauler, Thomas; Theurer, Sarah; Antke, Christina; Esposito, Irene; Kinner, Sonja; et al.
Highlights: accurate staging of breast cancer patients plays a pivotal role in treatment management. patients were examined by a traditional staging imaging and whole-body 18 F-FDG PET/MR. changes in therapy recommendations were evaluated. differences in therapy recommendations were seen in 14% of the cases. Current guidelines may consider systemic staging with 18 F-FDG-PET/MRI. Abstract: Purpose: To investigate whether potential differences in staging between a traditional staging imaging algorithm and 18 F-FDG PET/MR lead to a change in patient management in breast carcinoma and to compare the diagnostic accuracy between the traditional staging algorithm and 18 F-FDG PET/MR for the TNM classification. Method: In this prospective cohort study from two university hospitals 56 women with newly diagnosed, therapy-naive breast cancer and increased pre-test probability for distant metastases were included. All patients were examined by a traditional staging imaging algorithm (X-ray mammography, breast ultrasonography, chest plain radiography, bone scintigraphy, and ultrasonography of the liver and axillary fossa) and whole-body 18 F-FDG PET/MR including dedicated 18 F-FDG PET/MR breast examinations. Each patient was discussed two times in a separate tumor board session to determine a total of three therapy recommendations based on histopathological data of the primary tumor and (1) traditional algorithm only, (2) traditional algorithm and 18 F-FDG PET/MR, and (3) 18 F-FDG PET/MR only. Major changes in therapy recommendations and differences between the traditional staging algorithm and 18 F-FDG PET/MR for the TNM classification were evaluated. Results: Staging by 18 F-FDG PET/MR led to a difference in treatment compared the traditional staging algorithm in 8/56 cases (14%). Therapy changes included therapy of the breast, locoregional nodes and systemic therapy. A trend to staging superiority was found for 18 F-FDG PET/MRI without statistical significance (p = 0.3827). Conclusion: In conclusion, for breast cancer patients with elevated pre-test probability for distant metastases a change of the therapy regiment occurs in 14 % of patients when staged by 18 F-FDG PET/MR and confirmed by histopathology compared to a traditional staging algorithm. In particular with regard to the amendment of the guideline further assessment of 18 F-FDG-PET/MR in this setting is necessary to assess the true value of this modality.